(untitled)
This study deals with the foraminiferal assemblages of Plio-Pleistocene sediments of the northern side of the Peloritani Mountains (North-Eastern Sicily). Six sections were closely sampled in the surroundings of Rometta (Sottocastello Sud, Sottocastello, Torrione, Sperone, Sottorometta, Rometta